Mecanismos envolvidos na manutenção de inquilinismo obrigatório em ninhos de cupins - Cruz, Joseane Santos (2021)
Resource defense is a hallmark characteristic in animal kingdom. Eusocial insect nests facilitate the survival, maintenance and success of their colonies. Contrastingly, these nests are highly attractive environments for several other species. Termites of Inquilinitermes genus are specific obligate inquilines of Constrictotermes sp. (hosts) nests. Studies suggest that this relationship seems to be maintained via spatial segregation of cohabitants within the nests. In this study, we described how the cohabitation system Constrictotermes sp. x Inquilinitermes microcerus in Sergipe state differs from those observed in other Brazilian regions. Additionally, we analyzed whether the mechanisms involved in cohabitation are related to cues habituation or colony avoidance within the nests. We conducted aggressiveness and odor choice bioassays (body and intestinal) in host-inquiline pairings from the same and different nests. Our results showed that all sampled nests were epigeal and their dark walls (where the inquilines aggregate) are uniformly distributed, different from the pattern observed in other regions. Cohabitation was more likely to occur in nests larger than 20.07 L. No aggressive behavior was observed between host and inquiline, whether coming from the same or different nests. Both species had died quickly when kept in close contact with each other. Interspecific mortality was higher among hosts and inquilines from distant nests than among those from nests in the same location. Hosts were attracted to the inquiline body odor; while inquilines showed attraction to the intestinal and body host odor. In conclusion, our results suggest that there is host-inquiline recognition; however, without aggressiveness. This result could be explained by odor camouflage by the inquiline, as well as odor habituation by the host. Our results can contribute to a better understanding of the mechanisms involved in species coexistence in the small scale of nests.